(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The purpose of this study is to investigate the results that would be obtained by exchanging cement for metakaolin and fine aggregate for waste foundry sand. For the purpose of this inquiry, M-30 grade concrete is produced, and it is examined for characteristics of hardened concrete such as compressive strength. Samples with required dimensions were utilised with Metakaolin at a constant 10 percent, and the fine aggregate was replaced with waste foundry sand at weight percentages of 0, 10, 20, 30, and 40 percent. Based on the findings, it appears that improving the mechanical properties of concrete by mixing in Metakaolin and waste foundry sand is beneficial. The best results were obtained by replacing cement and sand with Metakaolin at a percentage of 10 percent and waste foundry sand at a percentage of 30 percent, respectively. The findings indicate that, up to a certain amount of Waste foundry sand and Metakaolin addition, there is a gain in mix strength; however, after that point, further addition of the Metakaolin and Waste foundry sand begins to lower mix strength. Despite the fact that adding Metakaolin and waste foundry sand up to a level of ten percent and thirty percent, respectively, helps in achieving higher strength than conventional concrete, the inclusion of these materials is not required. As a result, the use of metakaolin and waste foundry sand in place of traditional sand aids in the development of green concrete that is both kind to the environment and durable.